(untitled) (Research, Society and Development, 2020)
The studies involving post-harvest, characterization of pathogens and final destination of hortifruits residues are scarce in the literature. With this, you can obtain information about the marketing setting, the postharvest and the final destination of the pepper sold in the Chapadinha (MA) sector. The research included three stages: application of questionnaires, characterization of fruits and identification of pathogens. Questionnaires were applied through direct interviews in street markets/fairs, greengrocers, and supermarkets. For characterization of postharvest quality, you can purchase 30 peppers per segment, follow the step to identify pathogens, collect four sizes of peppers in two types of commercial use. At the end of the survey, we concluded that the peppers offered in Chapadinha (MA) come from other states, mainly Ceará (88.46%). The fruits follow Brazilian quality standards, but the open market stands out in terms of the characters analyzed. Grocery stores and supermarkets offer a significant amount, with high rates of occasional losses mainly due to physiological disorders. Postharvest diseases caused by Pectobacterium sp., Colletotrichum capsici, Colletotrichum gloeosporioides and Phytophthora capsici have been identified, such as those that may be related to the long procedure and inadequate postharvest practices since transport. The final destination of the losses is environmentally inadequate, although traders show the selectivity in the selection of food waste and the awareness that the directions most use. Thus, it is important to encourage the municipal public authorities to improve the actions for the disposal of organic waste, the final destination of which has been inadequate dumps.